NYERI PUNGGUNG BAWAH PADA IBU HAMIL TRIMESTER II DAN III - Kurniati Devi Purnamasari (Journal of Midwifery and Public Health, 2019)
Low Back Pain is a complaint of complex pain that occurs most frequently in the world and Indonesia. Lower back pain in pregnant women of the second and thrid trimester is a common complaint that often occurs among pregnant women, it is estimated that about 70% of pregnant women complain of some form of back pain at some time in pregnancy, labor until postpartum. This study was conducted to describe lower back pain in pregnant women in the third trimester. A cross-sectional descriptive study design, consecutive sampling was conducted in June 2018, using a questionnaire. Research subjects were pregnant women in the second and third trimester. There are 30 respondents entered the study, respondents who experienced mild pain as much as 20%, 50% experienced moderate pain and as much as 30% experienced severe pain accompanied by accompanying symptoms. Although it is a problem, 82% of teenagers just leave it when pain arises or just drink warm water and suppress the affected part (18%). In the second and third trimester pregnant women seek help from their husbands and families (87.2%) regarding problems that arise and only 12.8% of the second and third trimester pregnant women seek help from health workers /midwives. Most respondents have experienced lower back muscle pain. Generally, the information about the lower back is mostly obtained from other pregnant women and parents. When experiencing a lower back most pregnant women ask for help to their husbands and families. Health education about the problem of low back pain is important for the second and third-trimester pregnant mother, husband and family, and the need for routine evaluation of low back pain problems in the second and third-trimesterpregnant mothers by clinicians.Keywords: low back pain, second and third-trimester pregnant women